Al-Farabi in the studies of French philosophers (Journal of Philosophy Culture and Political Science, 2019)
In this article we are talking about the study of philosophy of al-Farabi in the studies of French researchers. The aim of the article is to study and consider the views of French researchers on the philosophical system of al-Farabi from the scientific and philosophical point of view. French researchers like Etienne Gilson, Baron Carra de Vaux, Henry Corbin, Alain de Libera, Philippe Vallat and others have an attractive study of the philosophy of al-Farabi. The study of the point of view of French philosophers shows that they basically consider al-Farabi to be a religious thinker and a representative of Sufism. They affirm in their studies that al-Farabi was not just a follower of Aristotle, but a philosopher, with a doctrine that is not only different from Aristotle’s teachings, but is also against it with his mystical inspirations. They also show that the goal of al-Farabi’s philosophy is to reconcile the teachings of Plato and Aristotle and by this way thinker wants to reconcile the philosophy with religion. In the process of research, the author used analytical, historical, systemic and comparative methods of analysis, which contributed to a comprehensive study of the problem. The results of the research are theoretical, methodological and scientifically practical, as they make it possible to understand the interpretation by modern French scientists of the philosophical views of al-Farabi on the problem of God, creation, world, soul, intellect, etc. The main provisions and conclusions of the article can be used in subsequent studies of the problems of ontology and gnoseology in eastern and western peripatetism. The results of the study can also be used in reading lectures and special courses on the history of philosophy.Key words: philosophy, Sufism, theologian, theology, French philosophers, mysticism, religion, thinker.